CHEMICAL CONCENTRATIONS OF POLLUTANT LEAD AEROSOLS, TERRESTRIAL DUSTS, AND SEA SALTS IN GREENLAND AND ANTARCTIC snow strata - Chow, Tsaihwa J.; Patterson, C.; Murozumi, M. (1969)
The report describes results of an analyses of lead in annual ice layers from the interior of northern Greenland and in annual layers of ice from the interior of the Antarctic continent. The observations of the chemical concentrations of the common elements in ice from the interior of Greenland and Antarctica can be explained in terms of simple relations among sea salts and terrestrial dusts. About ten times more dust was found in Greenland interior ice than in Antarctic interior ice, but twice as much sea salt was found in Antarctic interior ice than in Greenland interior ice. Prepared in cooperation with California Inst. of Tech., Pasadena. Div. of Geological Sciences, Contract AT(04-3)-427. Rept. no. CALT- 427-30 and Muroran Inst. of Tech., Hokkaido (Japan).